2019
DOI: 10.1194/jlr.m090464
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lysophosphatidylcholine-EPA enriches both EPA and DHA in the brain: potential treatment for depression

Abstract: The two major long-chain omega 3 FAs in animal tissues are EPA and DHA. Both of these FAs are known to have beneficial effects as anti-inflammatory agents and protect against various metabolic and neurologic diseases. Although the DHA concentration is higher than EPA in most tissues, the brain and retina are unique in having very high levels of DHA but virtually no EPA (1). The major dietary sources of EPA and DHA are fish, fish oil, and krill oil, all of which usually contain more EPA than DHA (2). However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 48 publications
6
51
1
Order By: Relevance
“…Whereas previous studies reported that brain EPA levels cannot be increased through diet 34,35 , we have demonstrated that feeding LPC-EPA to normal mice not only increases brain EPA levels by several fold, but also increases brain DHA by about 100% in normal mice 36 . We determined whether the increase in plasma BDNF can be used as a biomarker for the increase in brain EPA and DHA after feeding free and LPC-EPA.…”
Section: Effect Of Dietary Lpc-epa In Micecontrasting
confidence: 95%
See 1 more Smart Citation
“…Whereas previous studies reported that brain EPA levels cannot be increased through diet 34,35 , we have demonstrated that feeding LPC-EPA to normal mice not only increases brain EPA levels by several fold, but also increases brain DHA by about 100% in normal mice 36 . We determined whether the increase in plasma BDNF can be used as a biomarker for the increase in brain EPA and DHA after feeding free and LPC-EPA.…”
Section: Effect Of Dietary Lpc-epa In Micecontrasting
confidence: 95%
“…Animals and dietary treatments. Most of the analyses were carried out on samples obtained from our studies published previously 24,25,36,37 . All animal protocols were approved by the UIC institutional animal care committee, and all methods were carried out in accordance with the relevant guidelines and regulations.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we suggest that the failure of previous studies to show an increase in brain or retinal EPA was due to the inability of the supplements to generate LPC-EPA in vivo. We have previously shown that similar enrichment of brain EPA and retinal EPA occurred after feeding pure LPC-EPA [ 50 ]. Increasing retinal EPA in addition to DHA may be more beneficial than increasing only its DHA content, because EPA is the preferred substrate for the synthesis of VLCFA [ 51 , 52 ], which have unique functional significance in retina [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, most LC-PUFAs are thought to move from circulation across the blood brain barrier. Recent studies reveal that much of the acquisition of LC-PUFAs by the brain is mediated by a transporter, Mfsd2a, which moves n-3 and n-6 LC-PUFAs as lyso-GPCs from circulation across the blood brain barrier [49][50][51][52][53] . The current study shows that FADS variants are strongly associated with levels of n-6 and n-3 LC-PUFA-containing lyso-GPCs, including 1-arachidonoyl-2-lyso-GPC, 1-lyso-2-arachidonoyl-GPC, 1-docosapentaenoyl-2-lyso-GPC, and 1-eicosapentaenoyl-2-lyso-GPC, which are substrates for the Mfsd2a transporter.…”
Section: Discussionmentioning
confidence: 99%